Gender Equality from a Gender Budgeting Perspective - Maruzani, Nyevero; Matope, Nogget; Chauraya, Efiritha (International Journal of Asian Social Science, 2012)
Gender budgeting, which is also known as gender responsive budgeting , tracks how budgets respond to gender equality and women’s rights requirement. This entails investing in and making available mechanisms, guidelines and indicators that enable gender equality advocates to track progress, benefit incidence and show how supposedly gender neutral budgets impact on men and women. The aim of this discussion is to highlight the importance of gender budgeting in addressing gender disparities while taking note of the fact that gender is a key variable in development. The term gender budgeting will be defined in an effort to show how the practice can lead to gender equitable resource allocation and improve revenue generation for nations. This enables government’s commitment to gender equality and women’s empowerment move from paper to practical policies .In gender budgeting there is the creation of awareness regarding gender specific issues in the policies of all government agencies. It also brings to light the effort of women in running the economy and attaining economic efficiency by including equity in budget performance indicators .Considering that most nations signed and ratified international commitments on gender equality and equity, it is expected of them to put in place realistic budgetary measures towards the achievement of gender equality .Despite the fact that gender budgeting is a relatively new concept, it is undoubtedly an important ingredient in quickening the attainment of the Millennium Development Goals and the fulfilment of international commitments on gender equality. The discussion concludes by highlighting success stories of gender budgeting initiatives in various countries in an effort to show how gender budgeting can be used as a tool for engendering macroeconomic policies.